Konsep Tri Hita Karana dan sapta pesona pada desa wisata Penglipuran - Budiarta, I Putu; Meirejeki, I Nyoman; Putra Yudistira, Cokorda Gede; Kanca, I Nyoman; Arjana, I Wayan Basi (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2024)
The aim of this research is to review the tourist village of Penglipuran based on the theory of tourist destination. Penglipuran village is famous as one of the tourist destinations in Bali because of its society, which still preserves its traditional culture in its daily lives. The architecture of buildings and land processing still follows the concept of Tri Hita Karana, the philosophy of Balinese society regarding the balance of relations between God, humans, and their environment. Penglipuran Village succeeded in building tourism that benefited all of their communities without losing their culture and traditions. Penglipuran Village is one of the traditional villages in Bali that still maintains local wisdom until now. One of the local wisdom in Penglipuran village is the arrangement of a community spatial pattern that takes the Tri Mandala concept by dividing the roots into three zones. They are the main zone, middle, and Nista. Customs, values of mutual cooperation and kinship, as well as the local wisdom of the local community are based on the concept of Tri Hita Karana. The research method that we use is a qualitative method and a quantitative method to find bright spots from the papers that we made. The findings show that the tourist village of Penglipuran has already met the criteria as a tourist village destination and also meets the concept of Tri Hita Karana.